Wanita Karir dalam Bingkai Keluarga Sakinah - Muzayyanah (Al-Adillah: Jurnal Hukum Islam, 2022)
In the modern era, career women are in fact something that we cannot deny. Even though conceptually, it raises the pros and cons of thinking. On the one hand, career women are seen as moving towards equality with men. On the other hand, career women are seen as a step backwards in maintaining an eastern self-image. Based on this background, the objectives of this research are: 1). Knowing the efforts of career women in realizing a sakinah family. 2). Knowing the position of career women in the sakinah family. This research was conducted on female lecturers at Bondowoso University, using a descriptive qualitative approach, which attempted to describe some of the data obtained from the field, either by interview, observation, or documentation. Then proceed with the data analysis process. The results of this study indicate: 1). The efforts of women who have a career as lecturers at Bondowoso University in realizing a sakinah family include: a. Quality Time, in the sense that we must be able to maximize time with family, so that the importance of our existence is felt by them. b. Maintain good communication. c. Mutual open attitude. d. Mutual understanding. e. Time management. f. Husband's support for his wife for a career. g. Keeping the family intact. 2) Based on Islamic law, the position of a career woman in the concept of a sakinah family is to remain in the position of her husband so that she must still be obedient and obedient to her husband, because, in fact The husband is the leader of the family. eye of law.